Indoor optical wireless communications: Recent developments and future challenges - O'Brien, D (2009)
Wireless communications is facing the challenges of a predicted 'explosion' in the number of wireless devices, demand for higher capacity, and the need to reduce power consumption in order to lower greenhouse gas emissions. Optical Wireless (OW) communications may have a part to play in helping to achieve these aims. High speed line of sight optical wireless systems have the potential to provide a low complexity alternative to high frequency RF wireless communications, and may offer lower energy consumption. Visible light communications is also a growing area of interest. Low energy solid-state lighting sources can be modulated to provide data communications, and this can augment the communications provided by other wireless techniques. In this paper we review progress in these areas. Examples and results from systems will be reported, together with future directions and challenges. © 2009 SPIE.